ANALISIS PENGARUH PERDAGANGAN LINTAS BATAS MELALUI POS PEMERIKSAAN LINTAS BATAS (PPLB) ENTIKONG TERHADAP PERTUMBUHAN EKONOMI KAWASAN PERBATASAN DI KABUPATEN SANGGAU - ME, SUHARTY (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACK This research find that the contribution of border trade through Entikong Border Gate to Sanggau Regencys border area economic growth over the past 20 years was very small, one percent increase in export resulted in 0,03 percent in economic growth. Keyword : export and economic growth.